ANALISIS PENGARUH UPAH MINIMUM, RATA-RATA LAMA SEKOLAH, DAN STATUS KEWILAYAHAN TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN/KOTA PROVINSI JAWA BARAT, JAWA TENGAH, DAN JAWA TIMUR TAHUN 2024 - Hamda El Ramadani Poetra; Riswanti Budi Sekaringsih (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effect of minimum wage, average years of schooling, and regional status on the number of poor people in the districts/cities of West Java, Central Java, and East Java in 2024. The data used is secondary cross-section data obtained from relevant agencies. The analysis method used is multiple linear regression with an OLS approach logarithmic form and classical assumption testing. The results show that the minimum wage and regional status variables have a significant positive effect on the number of poor people while the average years of schooling variable has a significant negative effect. A robust model was used to overcome the heteroscedasticity problem detected in the model. The findings corroborate that education, regional characteristics, and minimum wage determine the poverty rate.